Penyembuhan Luka Jahitan Perineum Tehnik Jelujur Subkutikuler Lebih Cepat Dibanding Tehnik Terputus Sederhana - Rahayu, Dewi; Setya Arum, Dyah Noviawati (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background: Simple cut-off stitching technique was techniques used in perineum stitching wound management. With this technique 65% mom with perineum stitching wound was healed on the fifth day of post partum, 35% of its was healed on the tenth day of post partum. According to the data in Health Department of Riau Islands Province, the cause of maternal deaths in Riau Islands Province18% were caused by infections and 68% of them werecaused by perineum wound healing complications. One way to avoid the perineum wound healing complications was with sub kutikuler baste stitching technique that can accelerate the process of wound healing. Objective: To know the difference of perineum stitching wound healing time between simple cut-off stitching technique with sub kutikuler baste on post partum moms in Riau Islands Province Public Hospital 2012. Method: Experiments with post test time series with one control group design. The population in this study was all post partum moms in Riau Islands Province Public Hospital 2012. Samples taken with simple random sampling technique with consecutive sampling and set inclusion and exclusion criterias as much as 27 intervention group subjects and 27 control group subjects. The variable in this study was sub kutikuler baste stitching technique tailoring techniques and perineum stitching wound healing time. Data was analyzed using Mann Whitney Test. Result: The average of perineum stitching wound healing time differenceswith sub kutikuler baste stitching technique and simple cut-off was 2,2963 days. The statistical test results with Mann Whitney Test obtained p value 0,0000, where p < 0.05. Conclusion: There was time difference of perineum stitches wound healing time between simple cut-off stitching techniques and sub kutikuler baste on post partum moms in Riau Islands Province Public Hospital 2012